Mapping reading attitudes of high school students: Information mastery strategy - Mustika, Tria Putri; Zulhafizh, Zulhafizh; Rasdana, Oki; Pernantah, Piki Setri (Journal of Research in Instructional, 2023)
This research aims to analyze the reading attitudes of high school students in order to develop effective strategies to improve mastery of information through reading. The research was conducted using descriptive methods. The data source is students at the high school level with a limited sample of 31. The data collection technique is in the form of a questionnaire. Data analysis was carried out by observing the items that determine students' attitudes related to reading. The analysis process is strengthened by descriptive statistics. The results of the research show the order of students' reading attitudes from highest to lowest, namely: observing the title of the reading source before reading, looking for a safe environment, looking for reading friends, helping friends in understanding reading, looking for information related to the benefits of reading texts, reading anything, motivating yourself, asking friends or teachers if you don't understand, trying to do assignments, using free time to read, and implementing the principle of mandatory reading. All attitudes carried out by students have a positive impact on strengthening reading skills and ultimately broadening horizons and information.